Social-Philosophical Analysis Of The Phenomenon Of Tolerance (Eurasian Journal of Humanities and Social Sciences, 2026)
The article reveals the system of tolerance as one of the most urgent socio-philosophical problems of our time. The concept of tolerance is understood as being patient and tolerant towards the behavior, lifestyle, thoughts, speech, feelings, beliefs, and actions of others